Situational factors, sources of strain, and ethical considerations of self-employed individuals in conflict affected regions of Pakistan - Kamran, Hyder; Khan, Zaheer Ahmed; Alwie, Aryaty; Vasudevan, Asokan; Asim, Zeeshan (ANPAD - Associacao Nacional de Pos-Graduacao e Pesquisa em Administracao, 2024)
Objective: This study investigates the ethical dilemma of self-employed individuals in war and terrorism-affected areas. Specifically, this study examines how situational factors, sources of conflict, government intervention, and ethical considerations interact for self-employed individuals in terrorism-impacted areas of Pakistan's Khyber Pakhtunkhwa (KPK) province. Theoretical Framework: Grounded on strain theory and cognitive theory of depression we utilized a deductive approach under a constructivist view of social reality. Method: The study employed an explanatory research design using quantitative data. Interviews with focus groups enabled us to identify key variables explaining the local phenomenon. We used a structured questionnaire to collect data. Results and Discussion: The results revealed that situational factors (SF) significantly impact self-employed ethical concerns (ECSE). The indirect effect indicates a partially mediation by personal strain on relationship between situational factors and ethical concerns. However, government intervention (RGI) did not indicate moderating effect on the relationship between situational factors and ethical concerns of the self-employed. Research Implications: This study contributes to the literature related to ethical behaviour of self-employed individual. By exploring this relationship, policymakers and practitioners can better understand self-employed individuals in challenging environments. Originality/Value: The study is unique in that it examines a real-life situation in a province of Pakistan. The study justifies the research gap and interprets conceptual variables effectively through its model. This is the first study that analyses moral dilemmas faced by self-employed individuals under the influence of situational factors in terror-affected areas in Pakistan. Study results are based on a field survey and can provide meaningful insight into practical solutions.